Dental professionals' knowledge, attitudes, and practice behaviors related to human papillomavirus vaccination. (1st December 2019) - Patel, Seena; Koskan, Alexis; Spolarich, Ann; Perry, Maureen; Flood, Timothy
Abstract: Objectives: In Arizona, human papillomavirus (HPV)‐related cancers are declining, with the exception of oropharyngeal cancer (OPC). HPV‐related OPC is largely caused by persistent infection with oncogenic HPV strains, many of which the 9‐valent HPV vaccine offers protection. Little is known about dental professionals' willingness to promote the HPV vaccine to prevent OPC. The current study assessed Arizona dental professionals' knowledge, attitudes, willingness, and current practice behaviors related to HPV vaccine promotion. Responses between dentists and hygienists were also compared. Methods: A convenience sample of 711 dentists and hygienists attending a regional conference were recruited and asked to complete a 34‐item survey assessing knowledge and attitudes about HPV, the HPV vaccine, HPV‐related OPC, and their willingness to promote and administer the HPV vaccine. Fisher's exact tests and Mann–Whitney U tests were used for data analysis. Results: Most respondents answered HPV knowledge questions correctly but did not know HPV‐related OPC has a more favorable prognosis than other head and neck cancers. Dentists were more confident discussing and recommending the HPV vaccine. Both dentists and hygienists were willing to refer patients to their non‐dental primary care providers for vaccination; however, they were less confident in administering the vaccine if it fell within their scope of practice. They reported willingness to receive training to recommend the vaccine. Conclusions: Given the willingness of respondents to receive training related to HPV vaccine communication, future research should develop and test talking points and communication training to aid dentists and hygienists in their promotion of the HPV vaccine.